Mechanical and magnetic properties of composite materials with polymer matrix - Grujić A.; Talijan N.; Stojanović D.; Stajić-Trošić J.; Burzić Z.; Balanović Lj.; Aleksić R. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Many of modern technologies require materials with unusual combinations of properties that cannot be met by the conventional metal alloys, ceramics, and polymeric materials. Material property combinations and ranges have been extended by the development of composite materials. Development of Nd-Fe-B/polymer composite magnetic materials has significantly increased interest in research and development of bonded magnets, since particles of Nd-Fe-B alloys are proved to be very suitable for their production. This study investigates the mechanical and magnetic properties of compression molded Nd-Fe-B magnets with different content of magnetic powder in epoxy matrix. Mechanical properties were investigated at ambient temperature according to ASTM standard D 3039-00. The obtained results show that tensile strength and elongation decrease with an increase of Nd-Fe-B particles content in epoxy matrix. The modulus of elasticity increases, which means that in exploitation material with higher magnetic powder content, subjected to the same level of stress, undergoes 2 to 3.5 times smaller deformation. Scanning Electron Microscopy (SEM) was used to examine the morphology of sample surfaces and fracture surfaces caused by the tensile strength tests. The results of SQUID magnetic measurements show an increase of magnetic properties of the investigated composites with increasing content of Nd-Fe-B particles.